Transformative Justice Through Social Engineering: Analyzing the Role of Legislation in Supporting the Rehabilitation of Drug Addicts to Become Productive Members of Society - Widoyoko, Wredha Danang; Ngaisah, Siti; Haryono, Haryono; Rahmawati, Diah Ayu; Sanusi, Ruchan (West Science Interdisciplinary Studies, 2024)
The research investigates law's role in promoting transformative justice through social engineering, focusing on rehabilitation and reintegration processes of drug addicts into society. This study applies a normative-juridical approach to evaluate Indonesia's legal frameworks for their effectiveness in handling addiction as a public health issue. Comparative analyses with international models, such as the decriminalization in Portugal and harm reduction policies in the Netherlands, show what a change of heart in legal philosophy might achieve. The findings put forward the majors lacuna in the present legislation: undue punitive, lack of supportive infrastructure, and stigma among society. Recommendations offered by the study go on to include legislative reform for rehabilitation, supportive infrastructure development, public-private partnership for effective reintegration. This paper advocates for a compassionate justice system that embeds transformative justice principles into legal frameworks, promoting societal productivity and inclusivity.